Fuel Calibrator And Monitoring System For Automobiles (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Described herein is a method for fuel monitoring in a fuel tank of an automobile, the method comprisingchecking, using a control unit, whether time (t) greater than or equal to a predetermined time periodlapsed after the ignition of an engine of the automobile, if yes, initiating sampling of an output voltageusing a sensor based system having one or more pressure sensors disposed inside the fuel tank, checkingan output voltage (V) of at least one pressure sensor of the sensor based system, wherein the control unitchecks whether the sensor output voltage (V) is less than a predetermined value, and initializing anodometer reading counter (c).